(untitled) (Journal of Information Technologies in Education (ITE), 2008)
In article possible methods of construction of educational modules allowing are considered to diversify training processes in distance learning systems, to bring in convenient ways of interaction and the control over tutors and listeners, to use in studying processes and view phenomena visual interactive elements, to enable to make experiments in virtual simulators. Also questions of standardization of educational models are considered.